Qualitative and Quantitative Analysis of Native Food Products for Probiotic Properties - Bora; Suniti S, C. Ramalingam*, Pranay Bharadwaj, Pramod (Journal of Experimental Sciences, 2010)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Certain properties relevant to probiotic action, e.g. resistance to acid, bile tolerance, antibacterial activity, and antibiotic susceptibility were investigated of lactobacilli isolated from three kinds of Indian traditional fermented foods. Media of pH = 2.0–7.0 and bile salt concentrations of 0.3–1.0% were used as stress conditions. Antibacterial activity of the probiotic lactobacilli was determined by means of the Well diffusion test. The results revealed that the antibacterial activity of the three selected lactobacilli could inhibit all test pathogenic bacteria however at different inhibition levels. Among 7 isolates, only 3 strains (two from paneer and one from Ragi porridge) showed extremely high survival rates under stress caused by acid or bile salts. The three strains inhibited test pathogenic bacteria to different extents. They were sensitive to chloramphenicol, quinupristin, Chloramphenicol, Tetracyclin, Rifampicin and Streptomycin but resistant to Gentamicin, Vancomycin, Ciproflaxin and Penicillin G